Association of Tooth Loss in Chronic Periodontitis Patients with And Without Mellitus - DAVE, PAVITHRA H; S, BALAJI GANESH; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2021)
Tooth loss is a negative public health outcome that substantially affects not only the general and oral health status of people, but also their quality of life. Diabetes mellitus is one of the most widespread epidemics experienced worldwide; hence the aim of this study is to find the association of tooth loss in chronic periodontitis patients with and without diabetes mellitus. This cross sectional study consisted of a sample size of 547 patients of which 270 were diabetic patients and 277 were non diabetic patients and were distributed into two groups. After collection of data, it was tabulated with parameters such as name of the patient, age, gender, systemic condition, type of periodontal disease and tooth loss. The cast sheets of patients were obtained from the patient management software. The data of each patient was obtained and tabulated. The most common missing teeth were found to be upper anteriors and it had a higher prevalence of tooth loss in the non-diabetic group (26.82%) than in the diabetic group (18.43%). Association between tooth loss and systemic conditions was done using Chi square test p value- 0.008 and was found to be statistically significant. Tooth loss was higher in the age group of 61-70 years for the diabetic group and in the age group of 50-60 years for the non-diabetic group. The association between diabetes mellitus and periodontal disease is a well known fact. Therefore oral health education programs should be promoted in patients, which aids in early diagnosis and prevention of severe periodontal diseases.